Modelling of rational variants of the speed-skating technique - Voronov, A. V.; Lavrovsky, E. K.; Zatsiorsky, V. M. (Journal of Sports Sciences, 1995)
An 11-segment planar model of a speed skater's body was developed and computerized. The solution of the inverse dynamics problem made it possible to determine the net joint moments, reaction moments and the mechanical energy expenditures. The modelling of different variants of skating on the straight parts of the circuit revealed the most efficient one to be the run without arm swing, with the sideward push-off and without an active swing by the recovery leg.